2011
DOI: 10.1192/s1749367600002721
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder and attention-deficit hyperactivity disorder in Palestinian children affected by the war on Gaza

Abstract: The Gaza Strip has been badly affected by war and conflict over the past four decades. Palestinians are exposed to repeated incursions of the border areas, with many resulting casualties. At the end of December 2008, more than 230 Palestinians were killed and at least 770 were injured, including 100 in critical condition, after an Israeli airstrike. This was followed by a military operation that continued for 23 days, in which 1420 Palestinians, including 446 children, were killed. At least 4000 houses were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The Gaza Traumatic Events Checklist (GTEC) was the most commonly used tool to assess the EPV (n = 14) [ 28 – 30 , 33 , 37 , 39 , 41 – 45 , 47 , 50 , 51 ]. Modifications were made to the number and type of items examined in the different studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Gaza Traumatic Events Checklist (GTEC) was the most commonly used tool to assess the EPV (n = 14) [ 28 – 30 , 33 , 37 , 39 , 41 – 45 , 47 , 50 , 51 ]. Modifications were made to the number and type of items examined in the different studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported no significant relationship between proximity to the traumatic event and PTSD [ 34 ]. Fourteen studies reported that the most prevalent types of traumatic events were an indirect exposure, such as hearing drones and shelling artillery, and exposure to distressful events through the media [ 28 , 29 , 31 , 33 , 37 , 39 , 41 – 45 , 47 , 51 , 52 ]. Similar results were found among children and adolescents witnessing their fathers being detained by Israeli soldiers (n = 2) [ 40 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hypothesis here is that in extended families, because of the absence of the father, there might be a higher interference in the teenagers' personal lives from different family members; furthermore, also the presence of several adults with different opinions may induce more psychological stress, as also the lack of privacy and space for own choices in this extended family context. Above, participants living in refugee camps suffer more from psychosocial problems, which might be due to overpopulations and economic difficult living circumstances in refugee camps (Qouta, Punam€ aki, & El Sarraj, 2008;Thabet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%